Types of Deictic Units the Function of Deictic Units in an Artistic Text (Eurasian Journal of Learning and Academic Teaching, 2022)
It is important to keep in mind the importance of space and time events for communication activities. Each event takes place in a specific place and time, and the listener who receives information about this or that event seeks to know when and where it took place. In addition, for full disclosure of information, since any activity is performed by a specific person, information about the subject of that activity is also required.